BUREAUCRATIC SUPPORT-RELATED FACTORS AND THEIR RELATIONSHIPS TO THE IMPLEMENTATION OF A DECENTRALISED FISHERIES EXTENSION IN JAVA, INDONESIA - Waridin . (JOURNAL OF COASTAL DEVELOPMENT, 2002)
This study is aimed to assess the relationships between bureaucratic support-related factors and the implementation of decentralisation policy in fisheries extension. Population of this study comprised fisheries extension officers (FEOs) at the Rural Extension Centres (RECs) in Java, Indonesia. A multi-stage random sampling method was used for selecting the subjects of the study. A total of 50 FEOs at 10 districts in three provinces were covered. Data were collected from January to March 1998 by using interview and self-administered techniques. Descriptive statistics and correlation analyses were applied. Decentralisation policy in fisheries extension was not effectively implemented at the local level. Effectiveness in programme planning, decision-making, resources utilisation, and provision of benefits were not implemented as expected by the policy objectives. As beneficiaries of services, fishers received little from the implementation of decentralised fisheries extension. The effectiveness of the policy implementation was positively and significantly correlated to the bureaucratic support-related factors, which comprised of support from district government bureaucracy and supervision as well as guidance from related agencies.